2010
DOI: 10.1634/theoncologist.2009-0149
|View full text |Cite
|
Sign up to set email alerts
|

How Accurate Are Physicians in the Prediction of Patient Survival in Advanced Lung Cancer?

Abstract: Background. Because most cases of non-small cell lung cancer (NSCLC) are diagnosed at an advanced stage with a poor prognosis, patient inclusion in clinical trials is critical. Most trials require an estimated life expectancy >3 months, based on clinician estimates of patient survival probability, without providing formal guidelines. The aim of this study was to assess the accuracy of clinicians' predictions of survival in NSCLC patients (stages IIIB, and IV) and the possible impact of patient quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 30 publications
1
34
2
Order By: Relevance
“…We found, 11,13 that older and sicker patients are more likely to receive more accurate prognoses. Old age and poor health status are important indicators of poor prognosis, and thus, a greater number of estimates are accurate to within a year when patients are closer to death.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…We found, 11,13 that older and sicker patients are more likely to receive more accurate prognoses. Old age and poor health status are important indicators of poor prognosis, and thus, a greater number of estimates are accurate to within a year when patients are closer to death.…”
Section: Discussionmentioning
confidence: 65%
“…9 In general, reports on the prognostic accuracy of physicians conclude that physician estimates are inaccurate. [10][11][12][13] For example, in a large review article published in 2003 that is often cited as evidence of physician inaccuracy, Glare et al 11 found that in a population with median survival of 29 days, only 61% of physicians accurately estimated survival to within four weeks. In 1999, in another frequently cited example, Vigano et al 12 report that in a patient population with a median survival of 15 weeks, the median physician survival estimate overestimated actual survival by 1.1 months.…”
mentioning
confidence: 99%
“…8 Several studies showed that treating physicians tend to overestimate the duration of life. 9,28 Patients themselves tend to overestimate survival, and this can affect decision making. 29 In a study of patients with lung or colon cancer, those who thought they were going to live at least 6 months were more likely (OR 2.6) to choose life-extending therapy over comfort care compared with those who thought there was at least a 10% chance that they would not live 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9]11,12,14,15,21,23,28,29 The majority of reports that detail clinical outcomes in patients with primary or metastatic cancers note median survival expectations related either to specific cancer types or specific treatment paradigms. How reliable these median figures are when extrapolating to the unique situations of an individual patient are unknown.…”
mentioning
confidence: 99%
“…Intensivists are more pessimistic regarding clinical outcome of patients with cancer while using life support measures. Oncologists, on the other hand, tend to overestimate patient survival (20). Conflicts may arise during the care of critically ill cancer patients in the management of the same situation.…”
mentioning
confidence: 99%